Adoption of Internet Banking Service in Tanzania: The Influencing Factors among Customers of Commercial Banks - Kessy, Severine S. A. (University of Dar es Salaam Library Journal, 2021)
Information technology advancement has transformed the way banks deliver their services to their customers; as a result, internet banking is now in use. However, this type of banking is not fully utilised by customers in accessing banking products and services. This paper examined factors associated with customers ' adoption to internet banking services in Tanzania. Precisely, it assessed the influence of social environment, technology exposure and system capability on the adoption of internet banking services by customers. Cross section research design was used through survey strategy to collect data from the respondents. In this case, a questionnaire was administered among a total of 200 respondents from two big banks that were involved in the study. Data analysis was performed by using partial least squares structural equation to examine the relationship between internet banking adoption and influencing factors which included social environment, technology exposure and system capability. The results indicate that social environment, technology exposure and system capability are positively related to adoption of internet banking services by customers. The existing relationships and the results revealed the way in which the rate of adoption of internet banking services by customers can be increased. Among the observed challenges for adoption of internet banking services include limited awareness among the customers, network failure and instability as well as layout of web pages. It is therefore recommended that, banks should invest in bringing awareness to customers regarding the service by providing information and instructions, reducing the impact of network failure and having a well-designed and user-friendly website for easier use.